(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate the rate of infection and efficacy of antibiotics with and without removal of infected mesh in the operated patients of inguinal hernia repair with polypropylene mesh. Study Design: prospective observational study Place and Duration of study: This study was conducted at the Department of surgery, Baish general hospital, Kingdom of Saudi Arabia from June 2007 to December 2011. Materials and Methods: The male patients with ASA grade I & II were selected for the study. Their data was collected on SPSS-10. Diabetic patients were switched to short acting insulin perioperatively. Lichtenstein onlay mesh repair was performed with prolene mesh. Cefuroxime 1.5 g was given as prophylactic antibiotic at the time of induction of anesthesia, followed by three intravenous doses postoperatively. Results: Out of total 36 operated cases, two (5.55%) had infection of mesh. They started to discharge purulent material after a period of about six months of operation. Pus c/s revealed Staph. aureus. The bacteria were sensitive to all cephalosporin groups. Oral cephalexin was prescribed for seven days initially which suppressed the discharge for few days but restarted it after 2 weeks time of stopping the oral antibiotic. Ultimately the mesh was removed to resolve the infection. No recurrence was observed within I year of follow-up. Conclusion: Infection of mesh in inguinal hernia repair resolves after the infected mesh is removed.